M MANAJEMEN SEKOLAH DALAM MEWUJUDKAN KEGIATAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMA NEGERI 1 INDRALAYA - Yudia, Efran; Widayatsih, Tri; Fahmi, Muhammad (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
This study aims to describe school management in realizing the Pancasila Student Profile Strengthening Project (P5) at SMA Negeri 1 Indralaya. The research method used is qualitative. Data were collected using observation, interview, and documentation techniques. Data analysis used qualitative analysis. The results of the study showed that the implementation of all management functions-planning, organizing, implementing, and supervising have been well structured to support the objectives of the Pancasila Student Profile Strengthening Project (P5) program. In planning, the school has succeeded in identifying student needs, making a schedule with a semi-block system, and optimizing existing resources, although the involvement of external parties is still less than optimal. The organization of this activity has been clearly regulated through the division of committee tasks and the preparation of structured and detailed modules. The implementation of activities is guided by modules that are prepared together and implemented well. Supervision is carried out through joint monitoring for continuous improvement, which also went well. The management of the program activities has succeeded in going through structured management stages, although there are several aspects such as the involvement of external parties that still need improvement. Sustainability evaluation is key to ensuring the appropriateness and achievement of project objectives, as well as optimizing effective character value reinforcement.